Understanding and Improving Teamwork in Organizations: A Scientifically Based Practical Guide - Salas, Eduardo; Shuffler, Marissa L.; Thayer, Amanda L.; Bedwell, Wendy L.; Lazzara, Elizabeth H. (Human Resource Management, 2015)
Teams are pervasive in today's world, and rightfully so as we need them. Drawing upon the existing extensive body of research surrounding the topic of teamwork, we delineate nine “critical considerations” that serve as a practical heuristic by which HR leaders can determine what is needed when they face situations involving teamwork. Our heuristic is not intended to be the definitive set of all considerations for teamwork, but instead consolidates key findings from a vast literature to provide an integrated understanding of the underpinnings of teamwork—specifically, what should be considered when selecting, developing, and maintaining teams. This heuristic is designed to help those in practice diagnose team‐based problems by providing a clear focus on relevant aspects of teamwork. To this end, we first define teamwork and its related elements. Second, we offer a high‐level conceptualization of and justification for the nine selected considerations underlying the heuristic, which is followed by a more in‐depth synthesis of related literature as well as empirically‐driven practical guidance. Third, we conclude with a discussion regarding how this heuristic may best be used from a practical standpoint, as well as offer areas for future research regarding both teamwork and its critical considerations. © 2014 Wiley Periodicals, Inc.